A Study of a Method for Determining the Size of a Bremsstrahlung Focal Spot Using a Slit Collimator; Instruments and Experimental Techniques; Vol. 63, iss. 1 - Sorokin V. B. Vladimir Borisovich (2020, 2020)
Title screen